Differences in Learning Outcomes and Critical Thinking Ability of Students Taught Using Learning Video Media and PowerPoint with Problem Based Learning Model on Reaction Rate Material - Harahap, Syntia Wulandari; Simorangkir, Murniaty (Universitas Lampung, 2024)
Differences in Learning Outcomes and Critical Thinking Ability of Students Taught Using Learning Video Media and PowerPoint with Problem Based Learning Model on Reaction Rate Material. This study aims to determine the differences in learning outcomes and critical thinking Ability of students as well as the correlation between critical thinking Ability and learning outcomes of students taught using learning video media and powerpoint with problem-based learning models on reaction rate material. This research method is true experiment. The population of this study were all students of class XI IPA SMA Negeri 1 Lubuk Pakam and the sample was class XI J as the first experimental class taught with learning video media and class XI K as the second experimental class taught with powerpoint media taken using random sampling technique. The results showed that there were differences in learning outcomes and critical thinking Ability of students taught using learning video media and PowerPoint with problem-based learning models on reaction rate material. The average learning outcome of experimental class I was 89.67 and experimental class II was 85.33. The critical thinking ability of experimental class I was 77.67 and experimental class II was 69.87. There is a correlation between critical thinking Ability and student learning outcomes taught using learning videos of 0.837 with a very high category and using powerpoint of 0.796 with a high category. Keywords: Problem based Learning, Learning Video, Powepoint, Learning Outcomes, Critical Thinking AbilityDOI: 10.23960/jppk.v13.i1.2024.04